Ontela PicDeck (B) : customer segmentation, targeting, and positioning - Sawhney, Mohanbir S. ([London] : SAGE, 2016)
Ontela, a technology start-up company, has introduced an innovative service called PicDeck that improves the mobile imaging experience for wireless subscribers. Ontela sells PicDeck to wireless carriers, who in turn private-label the service to their subscribers. Ontela must decide which customer segments it should target for the service and how to create a positioning strategy and a marketing communication plan to promote it. This case outlines the factors which will influence Ontela's strategy.
Originally Published in: Sawhney, M., Grayson, K., Dupress, P., Hsu, C., Metzger, R., Obuchi, F., Sundaram, A., & Wilson, K. (2009). Ontela PicDeck (B): Customer Segmentation, Targeting, and Positioning (case revised 20/03/2015). 5-309-505(B). Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on online resource; title from home page (viewed on April 29, 2016).
Keywords: elektronické knihy; electronic books; Market segmentation -- Case studies; Target marketing -- Case studies; Wireless communication systems -- Case studies